Inverse association between ovarian cancer and the estimated glucose disposal rate in NHANES 1999–2018 - Zhang, Jing; Chen, Xianying; Wang, Yongjun (Frontiers in Cancer Control and Society, 2025)
ObjectiveInsulin resistance, a central feature of metabolic dysregulation, has been implicated in the pathogenesis of various cancers. However, the understanding of its role in ovarian cancer remains incomplete. This study explored the association between the estimated glucose disposal rate (eGDR), a robust indicator of insulin sensitivity, and ovarian cancer using data from the National Health and Nutrition Examination Survey (NHANES).MethodsWe analyzed data from 34,698 participants in the NHANES database, including 87 ovarian cancer patients and 34,611 controls. Propensity score matching (PSM) and multivariable logistic regression analysis were used to adjust for key confounders, such as race, education, poverty–income ratio, marital status, alcohol consumption, coronary artery disease diagnosis, heart failure diagnosis, triglycerides, total cholesterol, lymphocytes, and red blood cells. eGDR levels were evaluated as both continuous and categorical variables (quartiles), and restricted cubic splines (RCS) were utilized to assess the potential non-linear associations.ResultsThe eGDR level was significantly lower in ovarian cancer patients compared to the controls (6.94 ± 2.71 vs. 8.29 ± 2.52, P < 0.05). Multivariable logistic regression analysis demonstrated that the eGDR is a significant protective factor against ovarian cancer (OR: 0.826, 95% CI: 0.71–0.952, P < 0.05). Quartile analysis revealed a dose-dependent reduction in the prevalence of ovarian cancer with increasing eGDR (Q4 vs. Q1, OR: 0.283, 95% CI: 0.097–0.792, P < 0.05). RCS analysis confirmed there was a non-linear inverse relationship between the eGDR and the prevalence of ovarian cancer (P_non-linear = 0.005). Subgroup analysis further indicated that the subject's education level, marital status, and alcohol consumption significantly influenced the association between eGDR and ovarian cancer.ConclusionA significant inverse relationship was found between the eGDR and the prevalence of ovarian cancer, suggesting that a higher eGDR was a potential protective factor against ovarian cancer. These findings provide new insights into the mechanisms of ovarian cancer and highlight the potential of using the eGDR as a tool for early risk assessment and intervention.